Crossing stones - Frost, Helen, 1949- (New York : Farrar, Straus and Giroux, 2009)
Four young people in two families tell of their experience during World War I when the boys enlist and are sent to fight, Emma finishes school, and Muriel joins the suffrage movement.
"Frances Foster Books."
School Library Journal
Wilson's Junior High School
Wilson's Senior High School
Book Links (A.L.A.), January 2010
Booklist starred, October 2009
Keywords: Families -- Juvenile fiction; Friendship -- Juvenile fiction; Soldiers -- Juvenile fiction; Women -- Suffrage -- Juvenile fiction; World War, 1914-1918 -- Juvenile fiction; Family life -- Fiction; Friendship -- Fiction; Historical fiction; Novels in verse; Soldiers -- Fiction; War -- Fiction; Women -- Suffrage -- Fiction; World War, 1914-1918 -- Fiction; Family life -- Fiction; Friendship -- Fiction; Historical fiction; Novels in verse; Soldiers -- Fiction; War stories; Women -- Suffrage -- Fiction; World War, 1914-1918 -- Fiction; Michigan -- History -- 20th century -- Juvenile fiction; Michigan -- History -- 20th century -- Fiction; Michigan -- History -- Fiction; Historical fiction; War stories